2020
DOI: 10.1111/os.12688
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Hip Arthroscopy for Femoroacetabular Impingement in Chinese Patients Aged 50 Years or Older

Abstract: ObjectiveTo investigate the outcomes of hip arthroscopy for femoroacetabular impingement (FAI) in patients over the age of 50 years.MethodThis is a therapeutic case series study. A total of 27 FAI patients over the age of 50 years who met inclusion and exclusion criteria and were being followed up for at least 2 years in the orthopaedics department at our hospital between January 2015 and October 2017 were recruited for a prospective analysis on the outcomes of hip arthroscopy. All patients underwent unilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…This technique is also effective for middle‐aged and older adult patients. In a therapeutic case series study 26 , a total of 27 FAI patients over the age of 50 years were being followed up for at least 2 years. Imaging results and clinical follow‐up results showed that hip arthroscopy significantly improved hip symptoms and functions in Chinese FAI patients over 50 years without severe radiographic osteoarthritis (OA).…”
Section: Femoral Acetabular Impingement (Fai)mentioning
confidence: 99%
“…This technique is also effective for middle‐aged and older adult patients. In a therapeutic case series study 26 , a total of 27 FAI patients over the age of 50 years were being followed up for at least 2 years. Imaging results and clinical follow‐up results showed that hip arthroscopy significantly improved hip symptoms and functions in Chinese FAI patients over 50 years without severe radiographic osteoarthritis (OA).…”
Section: Femoral Acetabular Impingement (Fai)mentioning
confidence: 99%
“…The authors [ 1 ] from Daejeon, Korea report a therapeutic prospective case series. A total of 27 patients over the age of 50 years with femoroacetabular impingement (FAI) underwent hip arthroscopy were analysed.…”
Section: Outcomes Of Hip Arthroscopy For Femoroacetabular Impingement In Chinese Patients Aged 50 Years or Oldermentioning
confidence: 99%
“…3 This induces repeated microtrauma during certain movements, particularly flexion and internal rotation of the hip, leading to damage at the chondrolabral junction and osteoarthritis (OA) in some patients. 4 The initial management of FAI involves conservative measures with physiotherapy, 5 which may address associated conditions such as muscular imbalance, abductor fatigue, and extra-articular impingement. 6 When conservative treatment fails, surgery in the form of open surgical dislocation or hip arthroscopy (HA) can be offered.…”
Section: Introductionmentioning
confidence: 99%